Human Resources and E-Learning Effect on the Successful Study during the Pandemic Covid-19 - Siti Mardah; Muthia Harnida; Erni Alfisah (Hut Publication Business and Management, 2022)
The pandemic of Covid-19 has brought a big change in education, especially in the teaching and learning process. What used to be conducted physically in the class has suddenly changed to be conducted virtually through many digital platforms, such as Google Classroom, and media virtual such as Cloud, Zoom, Google Meet, etc. The change in the teaching and learning process from offline to online of course will affect both the students and the academic community. Those changes also can affect the successful study of the students. The research purpose is to find empirical evidence of the human resources of the academic community and the E-Learning effect on e-learning or what is sometimes called an online learning system for successful study. The samples are the students of the Faculty of Economics of Universitas Islam Kalimantan Muhammad Arsyad Al-Banjary Banjarmasin who join the Cost Management Classes. There are 75 students joined as participants through questionnaires that were delivered by Google Form. The analysis of data collection used multiple linear regression with SPSS 22. The result shows that human resources and E-learning positively and significantly affect the successful study of the students.